Lean Thinking : Application and Challenges to Implementation to Healthcare & Fertility Clinics - Kaur, Navneet (2009)
Although healthcare delivery systems have been slightly late to catch up with the ‘lean thinking’ concept, the organisations and specific departments that introduced it, have shown dramatic improvements in quality and efficiency. The Rainmaking fertility clinic needs lean thinking to be more responsive to customer needs and variability, to be more responsive to the stiffening competition, meet customer and regulatory demands for quality, and finally for operational efficiency, which can help reduce costs for the customers.The key Critical Success Factors identified for strong influence of lean thinking are tactful leadership and management traits, financial capabilities, skills and expertise of all levels of personnel and finally, the culture of recipient organisation.